Alcohol imagery and branding, and age classification of films popular in the UK - Lyons, Ailsa; McNeill, Ann; Gilmore, Ian; Britton, John (Oxford University Press, 2011)
Background: Exposure to alcohol products in feature films is a risk factor for use of alcohol by young people. This study was designed to document the extent to which alcohol imagery and brand appearances occur in popular UK films, and in relation to British Board of Film Classification (BBFC) age ratings intended to protect children and young people from harmful imagery.